Molecular investigations on the Rajanpuri strain of Beetal goat breed of Pakistan by complete mtDNA displacement region and microsatellite markers - Wajid, Abdul (Array, 2021)
The mitochondrial DNA sequences of DNA-D loops (mtDNA) from 105 individuals (11 Beetal goat Rajanpuri strains and 94 sequences extracted from GenBank) from 19 geographically and phenotypically defined domestic goat breeds in Pakistan were analysed in this experiment. In this study, we examined variability and molecular phylogeny of breeds. A total of 81 haplotypes were observed in 105 individuals, with a haplotype diversity of 0.984±0.006 and nucleotide diversity of 0.03953±0.00843. Phylogenetic analysis based on the mtDNA hyper variable segment (HVI) of the control region (481 bp), showed four mtDNA haplogroups (A, B1, C, and D) identified in Pakistani domestic goats, in which haplogroup A (84.11%) was dominant and widely distributed among all investigated breeds. The study revealed that all Rajanpuri strain haplotypes belonged to haplogroup A. The Rajanpuri is a rare local strain of Beetal goat breed located in western Punjab province of Pakistan. The results of genetic diversity based on 11 microsatellite loci revealed allelic diversity (3.6363) and high genetic diversity (0.8342) in the examined Rajanpuri goat breeds. The analysis for signature bottleneck events, using three models, revealed significant deviation of Rajanpuri goats from mutation drift equilibrium. The qualitative test of mode shift analysis also supported the results obtained under three models, indicating the presence of a recent genetic bottleneck in the Rajanpuri strain. This study provides the first information on the mtDNA architecture, genetic diversity and bottleneck analysis, which will be useful in the conservation and management of the highly valued Rajanpuri goat.